Morphology and Molecular Characterisation of Karenia mikimotoi (Dinophyceae) from Sabah Malaysian Borneo, with a Focus on the Second Internal Transcribed Spacer (ITS2) of Ribosomal RNA gene - SHERYL UNCHA, ANDREW CHIBA; SING TUNG, TENG; SAMSUR, MOHAMAD; NURSYAHIDA, ABDULLAH; ING KUO, LAW; PO TEEN, LIM; CHUI PIN, LEAW (UNIMAS Publisher, 2024)
The first recorded bloom of Karenia mikimotoi (initially Gymnodinium mikimotoi) occurred off the coast of Japan in 1934, causing mass mortality of shellfish and fish. This event highlighted the devastating impact of K. mikimotoi blooms and marked a turning point in harmful algal bloom (HAB) research, driving studies on its identification, biology, toxicology, and effects on marine life and ecosystems. The past reported bloom events in Southeast Asia have raised public concerns, leading to further investigation into the occurrence and geographical distribution of K. mikimotoi in the region. As of yet, there is no recorded evidence of K. mikimotoi blooms in Malaysian waters. This prompt the investigation of the occurrence and distribution of K. mikimotoi in Malaysia, and this study represent the first record of K. mikimotoi in Malaysian waters. In this study, clonal cultures of K. mikimotoi isolated from Sepanggar Bay, Sabah were examined using light microscopy (LM) and scanning electron microscopy (SEM) to observe its morphological features. Cells of K. mikimotoi from Malaysian Borneo exhibited a typical dorso-ventrally flattened body with bi-lobed and linear apical grooves on the cell apex. Molecular characterisation of the strains based on the internal transcribed spacer (ITS) region and large-subunit (LSU) ribosomal DNA revealed close phylogenetic relationships with other strains of K. mikimotoi from other regions, forming a monophyletic clade that positioned as sister to K. brevis, supporting the species identity of K. mikimotoi. The secondary structure of the ITS2 RNA transcript revealed a universal structure with four major helices. Structural comparison between K. mikimotoi and its relatives revealed four to six hemi-compensatory base changes. The results demonstrated the efficacy of ITS2 secondary structure information in delimiting species in Karenia. The detailed morphology and molecular characteristics of K. mikimotoi were revealed, for the first time, from the coastal waters of Malaysian Borneo.